Mapping Pollutant Concentration Using R Shiny Web Framework Visualization in Manado City - Rama Turnip; Winsy Ch. D. Weku; Eric Alfonsius (PT. SNN MEDIA TECH PRESS, 2026)
This study aims to develop a web-based application using the R Shiny framework to present interactive visualization of air quality data in Manado City. The main focus of this research lies in system design and user interface development to provide accessible spatial information for non-technical users. The application was implemented using the R programming language and supporting packages including shiny, leaflet, shinydashboard, and sf to facilitate map visualization and data management. Core features include an interactive dashboard, thematic map display with regional information, variable control panels, and structured database pages. System testing was conducted using Black Box Testing to ensure functional reliability according to user requirements. The implementation results demonstrate that the application successfully delivers responsive interactive visualizations and assists users in understanding air quality conditions through an informative and user-friendly web interface. Therefore, the R Shiny-based web application has potential as an effective environmental data visualization tool and can be further enhanced through continuous data integration and system performance improvements.